Economic Implications of Soybean Maturity Group, Herbicide Program, and Irrigation Requirement. Issue 1 (29th April 2016) - Wegerer, Ryan; Popp, Michael; Hu, Xiaoyan; Purcell, Larry C.
Abstract : Herbicide program, seeding rate, and seed technology interactions were analyzed using yield and irrigation tradeoffs for soybean [ Glycine max (L.) Merr.] Maturity Groups (MG) II through IV. Profit‐maximizing seeding rates were calculated and sensitivity analyses were performed. Results suggested that high seeding rates, affordable as a result of low seed cost, led to fast canopy closure which largely eliminated the need for postemergence herbicide use. Postemergence herbicide applications or early weed interference (in the case of the postemergence‐glyphosate [ N ‐(phosphonomethyl)glycine] program) may have resulted in some yield loss. Using MG IV soybean as opposed to earlier‐maturing soybean with lower water requirements was optimal over a wide range of soybean price and input cost assumptions. Larger, later‐maturing plants at high plant density contributed to competitiveness of soybean with weeds.